Measurement of the top quark mass in the tt[bar] → dilepton channel from √ s = 8 TeV ATLAS data - Aaboud, Morad; Anders, Christoph; Andrei, George Victor; Antel, Claire; Baas, Alessandra Edda; Brandt, Oleg; Djuvsland, Julia Isabell; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Geisler, Manuel Patrice; Giulini, Maddalena; Hanke, Paul; et al. (Physics letters, 2016)
The top quark mass is measured in the tt¯→dilepton channel (lepton=e,μ) using ATLAS data recorded in the year 2012 at the LHC. The data were taken at a proton-proton centre-of-mass energy of s=8 TeV and correspond to an integrated luminosity of about 20.2 fb−1. Exploiting the template method, and using the distribution of invariant masses of lepton-b-jet pairs, the top quark mass is measured to be mtop=172.99±0.41 (stat)±0.74 (syst) GeV, with a total uncertainty of 0.84 GeV. Finally, a combination with previous ATLAS mtop measurements from s=7 TeV data in the tt¯→dilepton and tt¯→lepton+jets channels results in mtop=172.84±0.34 (stat)±0.61 (syst) GeV, with a total uncertainty of 0.70 GeV.